Program Latihan Kebugaran Jasmani Mandiri Solusi Perkuliahan Pendidikan Jasmani Secara Daring - Fatkhur Rozi; Ibdaul Latifah; Setiorini Rahma Safitri; Dewi Wulandari (Biormatika : Jurnal ilmiah fakultas keguruan dan ilmu pendidikan, 2021)
The unfinished Covid-19 pandemic has an impact on all factors of life in society, one of which is education. The purpose of this study was to qualitatively describe the application of independent physical fitness training in physical education courses at IAIN Salatiga. This research is a qualitative descriptive study. The instrument is a researcher himself to collecting the data and analyzing it by way of reducing data, presenting data, and verifying it. The results of this study were a physical fitness training program carried out at IAIN Salatiga in Physical Education lectures, arranged in three stages; planning, implementation, and evaluation. This study concludes that independent physical fitness training for IAIN Salatiga students can be used as a solution during online physical education learning during the Covid-19 pandemic.